2010
DOI: 10.1111/j.1939-165x.2009.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein electrophoresis ofTrachemys scriptaandIguana iguana

Abstract: Background: Protein electrophoresis is widely applied in veterinary medicine, but is not used often in reptiles, in part because of lack of reference values. Objective: The goals of this study were to compare plasma protein profiles obtained by cellulose acetate electrophoresis (CAE) and agarose gel electrophoresis (AGE), measure precision and examine interference by sample hemolysis, and establish preliminary reference intervals for 2 reptile species. Methods: Heparinized plasma samples from healthy and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 16 publications
4
28
2
Order By: Relevance
“…Ranging from 2.2 to 5.5 g/dL, the normal total plasma protein concentration in reptiles is generally lower than that of mammals . Chelonians typically have lower albumin and higher globulin concentrations resulting in an overall lower A/G ratio …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranging from 2.2 to 5.5 g/dL, the normal total plasma protein concentration in reptiles is generally lower than that of mammals . Chelonians typically have lower albumin and higher globulin concentrations resulting in an overall lower A/G ratio …”
Section: Discussionmentioning
confidence: 99%
“…In our research, the albumin peak was identified unambiguously as the main first peak of each pherogram. We encountered difficulties in the identification of the main globulin subfractions (α1, α2, β1, β2) in some samples; therefore, we preferred to consider only one α and one β globulin fraction in the calculation of minimum–maximum ranges, based on the suggestion in an earlier report on the red‐eared slider, Trachemys scripta . Second, considerable inter‐ and intraspecific variation, enhanced by environmental factors including habitat, season, and diet, complicated the lineup of study data with previously reported data.…”
Section: Discussionmentioning
confidence: 99%
“…These fractions are believed to reflect over 200 proteins which function as part of the acute phase response and are broadly classified as alpha, beta, and gamma globulins (Kaneko, 1997). Fraction migration is quite varied by species, which often makes fraction identification challenging (Kaneko, 1997;Cray et al, 2007;Eckersall, 2008;Gimenez et al, 2010). As SPEP becomes more readily used with animal species, it is important to generate reference intervals as well as to standardize fraction delimitation so that results may be more comparable among different laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications in Veterinary Clinical Pathology ( VCP ) have demonstrated the use of this technique in very different animal species and in a variety of protein abnormalities 8–11 . However, cellulose acetate and agarose gel electrophoresis are still used as reported in previous papers in VCP 12–21 . Currently, most papers describe CZE in comparison with cellulose acetate or agarose systems.…”
mentioning
confidence: 99%
“…[8][9][10][11] However, cellulose acetate and agarose gel electrophoresis are still used as reported in previous papers in VCP. [12][13][14][15][16][17][18][19][20][21] Currently, most papers describe CZE in comparison with cellulose acetate or agarose systems. Because the resolution of CZE can be much higher than that of the other systems and proteins behave differently, reference values must be calculated again.…”
mentioning
confidence: 99%